263 PRENATAL DIAGNOSIS OF SIGNIFICANT STRUCTURAL HEART DISEASE BY ECHOCARDIOGRAPHY IN CLARK COUNTY, NEVADA, FROM 2004 TO 2006. Issue 1 (1st January 2007) - Acherman, R. J.; Evans, W. N.; Mayman, G. A.; Luna, C. F.; Rothman, A.; Collazos, J. C.; Restrepo, H.
Abstract : Background: Congenital heart disease (CHD) is a significant cause of perinatal mortality and morbidity worldwide. Its prenatal detection rate remains low in most parts of the world; an important proportion of infants with serious CHD are diagnosed only postnatally. Objectives: To evaluate the proportion of significant CHD prenatally diagnosed. Methods: This report includes data from 1, 546 patients seen from January 2004 to July 2006 by our group, which is the only referral group for pediatric cardiac evaluation in Clark County, Nevada. Study population is composed of all prenatal cardiac evaluations and all patients with significant CHD diagnosed in the first year of life, born in Las Vegas and without prenatal echocardiography. Results: From 775 fetal evaluations, 60 patients were diagnosed with serious CHD (8%); in all 60 patients, the prenatal diagnosis was confirmed at postnatal examination (100% accuracy). Of 771 patients with a CHD seen postnatally without prenatal evaluation, 130 patients were diagnosed with serious CHD (17%). The most frequent diagnoses were aortic coarctation/hypoplasia (17%), tetralogy of Fallot (16%), abnormal atrioventricular connections (13%), ventricular septal defects (10%), and hypoplastic left heart (6%). Conclusions: This study shows that only one-third of patients with serious CHD were diagnosed prenatally; therefore, further efforts should be made to encourage referring pregnant women who are suspected of carrying a fetus with CHD for prenatal cardiac evaluation.